Incorporating 1-butyl-3-methylimidazolium chloride ionic liquid into iota carrageenan solid biopolymer electrolyte for electrochemical devices application - Nur Azlina Abdul Ghani; Farah Hannan Anuar; Azizan Ahmad; Nadhratun Naiim Mobarak; Intan Juliana Shamsudin; Mariah Zuliana Dzulkipli; Nur Hasyareeda Hassan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Solid biopolymer electrolyte based on iota carrageenan and 1-butyl-3-methylimidazolium chloride, [Bmim]Cl were successfully prepared by solution casting technique. Weight percentage (wt. %) of [Bmim]Cl was varied from 0 wt. % to 100 wt. % and the highest ionic conductivity achieved was 2.70 × 10-3 S cm-1 for 70 wt. % [Bmim]Cl at ambient temperature. The interaction between iota carrageenan and [Bmim]Cl was confirmed by the formation of new peak on the ATR-FTIR spectrum. The reduction in crystallinity of iota carrageenan as the inclusion of [Bmim]Cl was observed based on X-ray diffraction (XRD) spectroscopy. FESEM morphology showed the compatibility and homogeneity between iota carrageenan and [Bmim]Cl while the LSV analysis showed that solid biopolymer electrolyte-based iota carrageenan-[Bmim]Cl possess high electrochemical stability up to 3.0 V. The transference number (TN) analysis indicated that ions are the main contributor for the ionic conduction.